Posttranscriptional destabilization of the liver-specific long noncoding RNA HULC by the IGF2 mRNA-binding protein 1 (IGF2BP1) - Hämmerle, Monika; Gutschner, Tony; Uckelmann, Hannah Julia; Özgür, Sevim; Fiškin, Evgenij Ilʹič; Groß, Matthias; Skawran, Britta; Geffers, Robert; Longerich, Thomas; Breuhahn, Kai; Schirmacher, Peter; Stoecklin, Georg; et al. (Hepatology, 2013)
Selected long noncoding RNAs (lncRNAs) have been shown to play important roles in carcinogenesis. Although the cellular functions of these transcripts can be diverse, many lncRNAs regulate gene expression. In contrast, factors that control the expression of lncRNAs remain largely unknown. Here we investigated the impact of RNA binding proteins on the expression of the liver cancer-associated lncRNA HULC (highly up-regulated in liver cancer). First, we validated the strong up-regulation of HULC in human hepatocellular carcinoma. To elucidate posttranscriptional regulatory mechanisms governing HULC expression, we applied an RNA affinity purification approach to identify specific protein interaction partners and potential regulators. This method identified the family of IGF2BPs (IGF2 mRNA-binding proteins) as specific binding partners of HULC. Depletion of IGF2BP1, also known as IMP1, but not of IGF2BP2 or IGF2BP3, led to an increased HULC half-life and higher steady-state expression levels, indicating a posttranscriptional regulatory mechanism. Importantly, HULC represents the first IGF2BP substrate that is destabilized. To elucidate the mechanism by which IGF2BP1 destabilizes HULC, the CNOT1 protein was identified as a novel interaction partner of IGF2BP1. CNOT1 is the scaffold of the human CCR4-NOT deadenylase complex, a major component of the cytoplasmic RNA decay machinery. Indeed, depletion of CNOT1 increased HULC half-life and expression. Thus, IGF2BP1 acts as an adaptor protein that recruits the CCR4-NOT complex and thereby initiates the degradation of the lncRNA HULC. Conclusion: Our findings provide important insights into the regulation of lncRNA expression and identify a novel function for IGF2BP1 in RNA metabolism. (Hepatology 2013;58:1703-1712)